Understanding Problems Encountered by Dyslexic Learners in Mathematics: A Qualitative Inquiry - Kunwar, Rajendra (Education and Development, 2022)
Dyslexic learners often experience difficulties in mathematics, which can hurt their academic achievement and future success. This study aimed to understand the problems encountered by dyslexic learners in mathematics. The study involved five dyslexic learners in grades V and VI from public schools in the Kathmandu Valley. Data were collected through in-depth interviews and analyzed using thematic analysis. The analysis revealed five themes: difficulty applying mathematical concepts, the impact of dyslexia on mathematics achievement, challenges related to language, comprehension, and memory, math anxiety and self-esteem, and individual differences and support systems. The results of this study highlight the need for targeted support and interventions that address the specific needs of dyslexic learners in mathematics education to improve their overall academic performance. It is recommended that a multi-faceted approach be implemented to support dyslexic learners in mathematics education, which should support the learners to overcome their challenges and achieve success in mathematics.